Influence of Smoking on Periodontal and Implant Therapy: A Systematic Review - Fahad Fayia AL-Qamshaa, Ruba Saleh Alduraibi, MAAZI AZIZ ALOTAIBI,Dr.Mashael Obaid AlShahrani, Saud Ahmed saeed alqahtani, Abdulaziz abdulrahman alqahtani, Misfer saeed alwadai, Saeed Saad Saeed Alshahrani (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Tobacco today considered one of the main causes of death, being associated with countless diseases such as: cancer, neurological, cardiovascular, and respiratory diseases. Smoking also has a negative effect on oral health which directly impairs treatment with dental implants. This current review aimed to evaluate the influence of smoking on dental implant failure rates and marginal bone loss (MBL). Materials and Methods: Electronic search was undertaken in three databases, failure and MBL were associated with follow - up time. Conclusions: Implants placed in smokers present a higher risk of failure than implants placed in non - smokers.